Estimation of Rainfall, Soil Erodibility and Crop Management Factors of the Universal Soil Loss Equation at Chandigarh. - Agnihotri, Y.; Sud, A.D.; Mittal, S.P.; Bansal, R.C. (Journal of Soil and Water Conservation, 2022)
Rainfall hyetographs from 1962-85 and soil loss data from two sets of runoff plots (sizes 22.13 In X 1.86 m and 90 m X 10 m) with a uniform slope of 1.5 per cent in both the cases during 1981--82 and 1984-85 were used to determine rainfall factor (El values), soil erodibility factor and crop management factor 'C' of maize grown with various crop combinations cultural practices. The average annual value of EI for Chandigarh works out to 767.3 mu, out of which 76 per cent alone is contributed by the months July to September. The average value of 'IC based on 4 years data has been determined as 105.75 kg/ha/El on the basis of EI values under various per cent chances and average value of K, the erosion potential of the Shivalik soils is estimated to be 0 ver 54, 77 and 98 tonnes/ha/year for 2.5 and 10 years recurrence intervals respectively as per USLE. 'C' factor for maize across the slope has been worked out as 0.435.